Relevansi Hukum Keluarga Islam dalam Tantangan Perkawinan Beda Agama di Era Modern - Zulfikar, Adznan Wijaya (Penerbit Goodwood, 2024)
Purpose: This study investigates the suitability and effectiveness of Islamic family law in addressing interfaith marriages amid modern societal challenges and evolving cultural dynamics. Research Methodology: The study employs a qualitative library research approach by analyzing scientific journal articles and research reports related to Islamic family law and the complexities of interfaith marriage in the modern era. Results: The research reveals that scholarly perspectives on interfaith marriage under Islamic family law are diverse. While some scholars maintain an absolute prohibition based on traditional religious texts, others advocate for more inclusive and contextual interpretations that consider evolving social realities. The implementation of interfaith marriages encounters significant legal and societal challenges, including formal restrictions, community resistance, and social stigma. These findings suggest the need for legal reforms and reinterpretations that align with contemporary values and promote religious tolerance, individual rights, and social harmony. Conclusion: Islamic family law must evolve through legal reinterpretation and inclusive regulatory frameworks to remain relevant and equitable in responding to interfaith marriage in modern contexts. Limitations: This research is based solely on secondary data and lacks insights from empirical fieldwork, limiting its ability to represent the lived experiences of interfaith couples and diverse Muslim communities. Contribution: The study contributes to ongoing discourse on reforming Islamic family law, emphasizing the importance of balancing religious principles with human rights, legal inclusivity, and social harmony in pluralistic societies.